2008
DOI: 10.1297/cpe.17.75
|View full text |Cite
|
Sign up to set email alerts
|

The Range of 2.2-3.3 mg/gCr of Pregnanetriol in the First Morning Urine Sample as an Index of Optimal Control in CYP21 Deficiency

Abstract: Auxological data are the gold standard indexes of the therapeutic conditions in patients with CYP21 deficiency over long-term periods, whereas urinary pregnanetriol (PT) for 24 h has been used as an index for short-term periods. We previously reported that the range of 1.2–2.1 mg/m2/day of PT for 24 h (24-h PT) could be used as an index of optimal control in patients with CYP21 deficiency. The purpose of this study was to analyze the range of PT in the first morning urine samples (morning PT) as an index of op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(25 citation statements)
references
References 9 publications
1
24
0
Order By: Relevance
“…The treatment in the three NC cases in the current study began earlier than recommended in the guidelines mentioned above because we believe that follow-up biochemical data, especially the peak serum cortisol level determined using the ACTH stimulation test and urine pregnanetriol levels, are important to achieve the goal of treating childhood 21-OHD. Notably, the ACTH stimulation test has already been established as a diagnostic method for adrenal insufficiency (28), and increased urine pregnanetriol levels have been previously reported to be associated with symptoms of childhood 21-OHD, such as pubarche and growth acceleration (21). Clin Pediatr Endocrinol…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The treatment in the three NC cases in the current study began earlier than recommended in the guidelines mentioned above because we believe that follow-up biochemical data, especially the peak serum cortisol level determined using the ACTH stimulation test and urine pregnanetriol levels, are important to achieve the goal of treating childhood 21-OHD. Notably, the ACTH stimulation test has already been established as a diagnostic method for adrenal insufficiency (28), and increased urine pregnanetriol levels have been previously reported to be associated with symptoms of childhood 21-OHD, such as pubarche and growth acceleration (21). Clin Pediatr Endocrinol…”
Section: Discussionmentioning
confidence: 99%
“…1a). At the last visit (age 12 yr), she received hydrocortisone (23 mg/m 2 /d) and fludrocortisone (0.05 mg/d); the doses were administered based on the assessment of overnight fasting pregnanetriol levels (21) and plasma renin activity before the drugs in the morning.…”
Section: Casementioning
confidence: 99%
See 1 more Smart Citation
“…Normalized 17-OHP suggests an overdose of glucocorticoids. Monitoring using pregnanetriol (PT), a urinary metabolite of 17-OHP, by urine collection has also been proposed ( 7 , 112 , 113 , 114 ). In a study of 21-OHD in Japanese children, excluding the neonatal and pubertal stages, a PT range of 1.2–2.1 mg/m 2 /d was shown to indicate good control ( 113 ).…”
Section: Treatment Monitoring For Growing Childrenmentioning
confidence: 99%
“…The target for 17OHP is reportedly 4-12 ng/mL before early morning medication, but this information is not based on auxological data ( 9 , 10 ). Our previous studies demonstrated that morning urine PT can be used as an index of control in prepubertal patients with 21-OHD based on height velocity, body weight, and bone age ( 11 , 12 ). According to these studies, 2.2-3.3 mg/gCr (95% confidence interval (CI) for the mean) and 0.59-6.0 mg/gCr (10th - 90th percentile) were proposed as the optimal range for the first morning urinary PT value ( 12 ).…”
Section: Introductionmentioning
confidence: 99%